Penerapan Disiplin Positif Bagi Siswa Mts Ciwedus - Hana Nurzakiah; Vany Dwi Putri; Fitri Amelia; Khamdiallah Khamdiallah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Students are the nation's successors, so students need to have good morals and morals. This character will grow through the family, school and community environments. One way to instill good morals and morals is through discipline at school. The words discipline are sometimes a scourge for students, because some teachers still apply violence in disciplinary education. Punishment is not an effective method for creating self-control in students. The punishment imposed will encourage bullying at school. The impact of punishment has a negative impact on students not only physically but also mentally. Therefore, it is necessary to apply positive discipline in every school, because by implementing positive discipline, long-term self-discipline will be created. This research on the application of positive discipline was carried out at Mts PUI Ciwedus Kuningan. We hope this research provides a new picture of nonviolent discipline patterns. It is hoped that this research will provide a new picture of non-violent discipline patterns when examining incidents of teacher violence for disciplinary reasons.